Detection of Helicobacter pylori associated antigen and heat shock protein 60 on follicular dendritic cells in the germinal centres of low grade B cell lymphoma of gastric mucosa associated lymphoid tissue (MALT). Issue 5 (May 1998) - Kobayashi, K; Yokota, K; Yoshino, T; Kawahara, Y; Dey, A; Hirai, Y; Oguma, K; Akagi, T
Abstract : AIMS: To investigate the localisation of Helicobacter pylori antigens and the expression of human heat shock proteins (HSP) in stomachs affected by MALT lymphoma. METHODS: Surgically resected stomachs from 24 patients with MALT lymphoma were immunostained with anti-H pylori rabbit antibodies (ORP-1 and ORP-2) and anti-human HSP60 mouse monoclonal antibodies (mAb) (LK-1 and LK-2). RESULTS: Follicular dendritic cells of germinal centres in the stomachs affected by MALT lymphoma were immunostained with anti-H pylori polyclonal antibodies and with anti-human HSP60 mAb, as were the epithelial cells. None of the lymph node samples reacted. CONCLUSIONS: Human HSP60, which cross reacts with anti-H pylori polyclonal antibodies, is often expressed on follicular dendritic cells in gastric MALT lymphoma tissues and may be aetiologically relevant to lymphomagenesis of MALT lymphoma.